Historical Aspect of the Development of the Industrial Production Index in the System of Official Statistics of Ukraine - Antonova, Natalia (Lithuanian Journal of Statistics, 2014)
This document shows the evolution of calculation of the industrial production index in Ukraine. Since theSoviet Union collapsed, in order to adapt Ukraine’s industrial statistics to the conditions of a market economy andinternational standards, especially of the EU and the UN, a series of notable improvements were implemented in themethodology for the calculation of the industrial production index. Ultimately, according to the methodology for theindustrial production index calculation introduced in 2009, which is currently implemented in Ukraine, the index isconstructed by methods used in statistical practice in the majority of countries all over the world and the European statisticalservice (the so-called method of permanent set of goods). The article also describes the features of the construction of theindex of industrial production in Ukraine in accordance with this methodology.